2018
DOI: 10.2147/cmar.s165804
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of concurrent chemoradiotherapy plus S-1 adjuvant chemotherapy on curative effect for treatment of patients with N3 stage nasopharyngeal carcinoma

Abstract: IntroductionThe purpose of this study was to analyze the efficacy and safety of concurrent chemoradiotherapy plus S-1 adjuvant chemotherapy for N3 stage nasopharyngeal carcinoma (NPC).MethodsThis study included 44 N3 stage NPC patients treated with concurrent chemoradiotherapy plus S-1 adjuvant chemotherapy. The intensity-modulated radiation therapy doses were planning target volume (PTV) 70–72 Gy for gross disease in the nasopharynx and 66–70 Gy for positive lymph nodes. The doses for high-risk- and low-risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…A retrospective study has shown that the oral fluorouracil analog tegafur can effectively reduce the rate of distant metastasis in patients with NPC with high metastatic risk . Maintenance chemotherapy with S1 and capecitabine in a variety of metastatic cancers effectively improves the OS and has tolerable toxicity . Our results are consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…A retrospective study has shown that the oral fluorouracil analog tegafur can effectively reduce the rate of distant metastasis in patients with NPC with high metastatic risk . Maintenance chemotherapy with S1 and capecitabine in a variety of metastatic cancers effectively improves the OS and has tolerable toxicity . Our results are consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Only three patients were required to reduce the dose of MC and were unwilling to continue with their therapy due to the grade 2 leukopenia. The gastrointestinal toxicities and stomatitis are other commonly reported toxicities of MC with S-1 [5]. However, as demonstrated in this study, only one patient (4.5%) encountered grade II gastrointestinal toxicities and no nephrotoxicity was observed.…”
Section: Discussionsupporting
confidence: 52%
“…Despite of the fact that several high level studies had verified that compared to concurrent chemoradiotherapy (CCRT) alone, adjuvant chemotherapy (AC) following CCRT (CCRT-AC), which is hypothesized to eradicate micrometastases, had not achieved survival benefits in advanced NPC [1]; although it had been thought to benefit survival of N3-NPC patients [4, 5]. However, intensive AC should be conducted cautiously due to potential patient intolerance to chemotherapy that can result from the acute toxicity of CCRT [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasopharyngeal carcinoma (NPC) is the most common head and neck cancer in southern China, affecting 30 out of 100,000 people. It is usually diagnosed with a high degree of malignancy and consequently leads to >34,000 deaths annually 1. Currently, the primary treatment modality for NPC is radical radiation therapy, with chemotherapy as an auxiliary option.…”
Section: Introductionmentioning
confidence: 99%